An Analysis of Students’ Drawing and Labelling Skills in Science at the Elementary Level - Dhar, Debarati; Gowramma I.P. (INDIAN EDUCATIONAL REVIEW, 2017)
Science, with its emphasis on facts and knowledge, is incomplete without skills like observation, interpretation, and analysis. One of the media through which they are expressed is drawing and labelling. There is especially unique need of drawing and labelling skills in biology because of the variety, complexity and intricacy of the diagram and the role it has on developing the concept. The purpose of this paper is to investigate and analyse the strengths and weaknesses of students in drawing and labelling skills and to determine the improvement in these skills after implementing intervention. Class VII students constituted the target population and were selected using purposive sampling. Both exploratory as well as experimental research designs were used. A pre-test post-test single group design was adopted. The data obtained was analysed using both descriptive and inferential statistics. Results indicated that majority of the respondents lacked all the 10 drawing and labelling skills tested. This casts doubt on the students’ understanding of biological concepts and hence their overall performance in the subject. After planned intervention, though there was a gain in skills, significant variation in gain percentage was observed indicating individual uniqueness. This suggests the need for using a variety of approaches to develop drawing skills.